Application of linked stress release model to historical earthquake data: comparison between two kinds of tectonic seismicity - Lu, Chunsheng; Vere-Jones, D. (Birkhaeuser Verlag AG, 2000)
The linked stress release model, incorporating a slow buildup of stress within a seismic region, its stochastic release through earthquakes and transfer between seismic regions, is applied to fit historical data from two typical kinds of seismicity: earthquakes occurring in intraplate (North China) and plate boundary (New Zealand) regions. The best model among different modifications of the basic model, which may reflect on a possible geophysical mechanism for earthquake occurrences, is obtained in terms of Akaike information criterion. For both tectonic regions studied, the linked stress release model fits the New Zealand data better than a collection of independent simple models, but is nearly indistinguishable from the simple stress release model in the case of North China. The seismicity in a plate boundary region due to subduction is more active and complex than that in an intraplate region due to collision between tectonic plates. The results highlight the major differences in tectonic seismicity, especially the heterogeneities of tectonic stress fields, and dynamic triggering mechanism with evidence that the crust may lie in a near-critical state.